Keberkesanan Kelas Agama di Masjid Daerah Hulu Langat Selangor - Abdul Kadir, Fakhrul Adabi (Jurnal Usuluddin, 2007)
The role of mosque as a centre of studies cannot be denied. Hence, most of the mosques in Malaysia have organised religious class programmes as their main activities. These efforts are their contributions in developing quality society and knowledgeable persons. This study aims to identify how far the religious classes set up by the mosques at the District of Hulu Langat Selangor Darul Ehsan be capable of enhancing knowledge and practice of those who attended the classes. The methodology of collecting datas used in this study are questionaire, interview and observation. Based on the findings, several opinions have been made and the most important point is that it is hoped all parties concerned with the proggrames can build an excellent relationship in the future.